Social Barriers to Economic Development in Kermanshah Province - vakil ahmadi; omid mansouri; nadie rezaei (توسعه اجتماعی, 2023)
In this article, an attempt has been made to examine the social barriers to economic underdevelopment in Kermanshah province. In order to obtain the appropriate results, a conceptual model has been used, the basic concept of which is the experience of demographic transition. In this paper, the mechanism of underdevelopment in Kermanshah province has been analyzed with the systematic grounded theory of Strauss and Corbin. A paradigm model was obtained in relation to the subject, which consists of: causal conditions (inappropriate demographic transition, ethnic and kinship relations and networks, migration flows and economic socialization); Intervention conditions (land reform and war); Background conditions (speed of change, type of change and type of training); Strategies (intra-group trust, emigration, especially elite, degree orientation, consumerism (women and the new generation) and social nihilism). This system has led to consequences such as inability to produce and creativity, intensification of migration flows, reproduction of anti-development mentalities, lack of capital accumulation and its outflow, and so on. The most important conclusion that is inferred from this study is that inappropriate demographic transition is an unthinking reality in the underdeveloped process of Kermanshah province. In addition to this, there are mental barriers and deadlocks such as kinship relations and economic socialization, etc., which are inherent in these barriers. At the same time, anomalies such as war, migration, etc. also have a profound effect in this regard. Finally, this article shows how obsolete attitudes such as intra-group trust, degree orientation and anti-development mentalities have hindered the economic development of Kermanshah province.